Role of initiating nucleoside triphosphate concentrations in the regulation of influenza virus replication and transcription. - Vreede, F; Gifford, H; Brownlee, G (2008)
The mechanisms regulating the synthesis of mRNA, cRNA, and viral genomic RNA (vRNA) by the influenza A virus RNA-dependent RNA polymerase are not fully understood. Previous studies in our laboratory have shown that virion-derived viral ribonucleoprotein complexes synthesize both mRNA and cRNA in vitro and early in the infection cycle in vivo. Our continued studies showed that de novo synthesis of cRNA in vitro is more sensitive to the concentrations of ATP, CTP, and GTP than capped-primer-dependent synthesis of mRNA. Using rescued recombinant influenza A/WSN/33 viruses, we now demonstrate that the 3'-terminal sequence of the vRNA promoter dictates the requirement for a high nucleoside triphosphate (NTP) concentration during de novo-initiated replication to cRNA, whereas this is not the case for the extension of capped primers during transcription to mRNA. In contrast to some other viral polymerases, for which only the initiating NTP is required at high concentrations, influenza virus polymerase requires high concentrations of the first three NTPs. In addition, we show that base pair mutations in the vRNA promoter can lead to nontemplated dead-end mutations during replication to cRNA in vivo. Based on our observations, we propose a new model for the de novo initiation of influenza virus replication.